Cultural Sensitivity among Tamil Linguistic Minority Students - S., SRUTHI; K.P., SEEMA MENON (JOURNAL OF INDIAN EDUCATION, 2025)
Education plays a key role in increasing cultural sensitivity by teaching students to be aware of different cultures, traditions and perspectives. To gain insight into how students from the Tamil linguistic minority group interact with and appreciate different cultures, their cultural sensitivity needs to be studied. In the pursuit of investigating the research problem, a simple random sampling technique was employed to select participants within the Kerala. The sample for the present study consisted of 200 Tamil linguistic minority students. A survey Methodology was employed, and statistical analyses, including percentages, means, standard deviations and t-tests were conducted to evaluate the hypotheses. The study reveals that Tamil linguistic minority students possess different levels of cultural sensitivity, and also that there exists significant difference in the mean scores of cultural sensitivities to gender, locale and type of management of schools. To improve cultural sensitivity among Tamil language minority students, targeted educational programmes should be implemented, intercultural interactions should be promoted and diverse perspectives should be included in the curriculum